Regulation and Function of Metal Uptake Transporter NtNRAMP3 in Tobacco - Kozak, Katarzyna; Papierniak-Wygladala, Anna; Palusińska, Małgorzata; Barabasz, Anna; Antosiewicz, Danuta Maria (Frontiers in Plant Science, 2022)
NRAMP genes encode proteins (Natural Resistance-Associated Macrophage Protein) with low substrate specificity, important for maintaining metal cross homeostasis in the cell. The role of these proteins in tobacco, an important crop plant with wide application in the tobacco industry as well as in phytoremediation of metal-contaminated soils, remains unknown. Here, we identified NtNRAMP3, the closest homologue to NRAMP3 proteins from other plant species, and functionally characterized it. An NtNRAMP3-GFP fusion protein was localized to the plasma membrane in tobacco epidermal cells. Expression of NtNRAMP3 in yeast was able to rescue growth of Fe and Mn uptake defective fet3fet4 and smf1 mutant yeast strains, respectively. Furthermore, NtNRAMP3 expression in wild-type Saccharomyces cerevisiae DY1457 yeast strain increased sensitivity to elevated concentrations of Fe, Mn, Cu, Co, Ni and Cd. Taken together, these results point to a possible role in the uptake of metals. NtNRAMP3 was expressed in the leaves and to a lesser extent in the roots of tobacco plants. Its expression occurred mainly under control conditions and decreased very sharply in deficiency and excess of the tested metals. GUS-based analysis of the site-specific activity of the NtNRAMP3 promoter showed that it was primarily expressed in the xylem of leaf blades. Overall, our data indicate that the main function of NtNRAMP3 is to maintain cross homeostasis of Fe, Mn, Co, Cu, Ni (also Cd) in leaves under control conditions by controlling xylem unloading.